Poliaminas na mitigação do estresse hídrico em plantas de milho - Esteves, Giovana (2022)
Plants are sessile organisms capable of adapting to different environmental conditions. However, climate changes such as temperature increase, irregular rainfall distribution, sea level rise, have influenced food production. Among these changes, the most severe for production is the water deficit generated by prolonged droughts. Corn (Zea mays L) is a cereal that suffers great losses with water deficit in Brazil and in the world. Its Brazilian production in 2022 reached 112.3 million tons, and could reach drops of up to 100% due to the lack of water in the different stages of development. It is an important vegetable for feeding humans and animals, in addition to its economic appeal for biofuel. Seeking a way to ensure a good development of the culture even under water stress, the priming of polyamines, spermine and spermidine were used in corn seeds. The drought sensitive hybrid BRS 1030 was used. Corn seeds were priming with spermine or spermidine, transferred to gerbox-type boxes containing sand and mannitol to mimic the effect of water stress (drought) and then cultivated for 15 days in a BOD-type chamber at 30 °C. and photoperiod of 12/12. Plant development was evaluated through its emergence and growth, chlorophyll fluorescence parameters and biochemical parameters such as enzymatic activity, sugar accumulation and influence of polyamines on cell division at root tips. With this it was verified that there is no difference in the germination percentage, however the use of polyamines affects the germination speed. Spermine favors the development of roots and carrying parameters related to it, such as length and root volume, increases the concentrations of sugars in the roots. While spermidine acts mainly on the shoot favoring development and protecting the photosystem. Both polyamines enhance antioxidative enzyme activity. However, the action of the polyamines separately is more effective when the plant is in optimal hydration conditions. It is concluded that spermine and spermidine used alone, at concentrations of 10 and 50 μM are not capable of effectively mitigating the effects of water stress, but the study of their combination is of interest since they act differently on plant development.